Community Application of Agroforestry in Sigi District, Indonesia - Rafiuddin; Rachman, Imran; Alam, Andi Sahri; Rajindra; Yani, Ahmad (International Journal of Psychosocial Rehabilitation, 2020)
- Short and long biological production systems in a way that is based on the principle of sustainability, simultaneously or sequentially both within the forest area and outside the forest area. The purpose of this study was to determine the agroforestry patterns used on community land in Bakubakulu Village. This research was conducted for three months, from October to December 2018. Respondents in this study used a purposive sampling technique. Data were analyzed using descriptive methods - the results of research on the age of the dominant respondents at the age of 21-30 years. The general education level of the respondents is a secondary school. The respondent’s length of stay is more than 30 years. The area of dominant respondent’s land is 0-1.5 Ha. The agroforestry pattern applied by respondents based on the time dimension is Intermittent on sloping ground and Coincidental on flat ground. According to the spatial aspects of the model used by respondents are Temporary Regular on flat land and Random Permanent on sloping land. The types of plants most widely planted by the community are candlenut, sugar palm, cocoa, clove, and coconut. And the Ordinary Temporary Pattern is the pattern most often applied by respondents.